Leposlovne slikanice o prevoznih sredstvih Vesne Radovanovič - Batič, Janja; Haramija, Dragica (Revija za elementarno izobraževanje, 2012)
Belletristic Picture Books on Means of Transport by Vesna Radovanovič. This article introduces six picture books written by Vesna Radovanovič and illustrated by Ana Razpotnik Donati and Maja Lubi, namely, Aljažev čevelj, Belo jadro, Dedkovo kolo, Mavrični balon, Puhačka, and Rožnati avtobus. As the stories were published as picture books, the article focuses on both key elements of a picture book, that is, the verbal narrative and the illustration, which together form a literary and artistic monolith. In terms of form and genre, picture books are classified as realistic and fantastic short prose works, where the prevailing genre principle is experiential prose featuring a small child as the main literary character. In the centre of the story there is a child's wish that will come true in the end. What distinguishes the picture books discussed herein is the power of the artistic expression of the two illustrators. While Ana Razpotnik Donati artfully combines various artistic elements to form an inseparable whole, paying attention to details and adding visual narrative to the story, Maja Lubi depicts in particular the underlying mood of the story.
Keywords: Vesna Radovanovič; Ana Razpotnik Donati; Maja Lubi; picture book; means of transport